Some Results on the Norm Attainment Set for Bounded Linear Operators on Smooth Banach Spaces - Johnny, Saied A.; Ahmed, Buthainah A. A. (Iraqi Journal of Science, 2021)
In this paper, we give new results and proofs that include the notion of norm attainment set of bounded linear operators on a smooth Banach spaces and using these results to characterize a bounded linear operators on smooth Banach spaces that preserve of approximate - -orthogonality. Noting that this work takes brief sidetrack in terms of approximate - -orthogonality relations characterizations of a smooth Banach spaces.